Stemness inhibition by (+)-JQ1 in canine and human mammary cancer cells revealed by machine learning - Marção, Maycon; Müller, Susanne; Xavier, Pedro Luiz P.; Malta, Tathiane M. (Frontiers in Drug Discovery, 2022)
Stemness is a phenotype associated with cancer initiation and progression, malignancy, and therapeutic resistance, exhibiting particular molecular signatures. Targeting stemness has been proposed as a promising strategy against breast cancer stem cells that can play a key role in breast cancer progression, metastasis, and multiple drug resistance. Here, using a one-class logistic regression machine learning algorithm (OCLR), we provide the stemness index (mRNAsi) of different canine non-tumor somatic and pluripotent stem cells and canine mammary cancer cells. We confirm that inhibition of BET proteins by (+)-JQ1 reduces stemness in a high mRNAsi canine cancer cell. Furthermore, using public data, we observed that (+)-JQ1 can also decrease stemness in human triple-negative breast cancer cells. Our work suggests that mRNAsi can be used to estimate stemness in different species and confirm epigenetic modulation by BET inhibition as a promising strategy for modulating the stemness phenotype in canine and human mammary cancer cells.